Bridging Boundaries: The Role of the Indian Diaspora in South Africa’s Anti-Apartheid Struggle (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The story of the Indian diaspora in South Africa—largely descendants of indentured labourers and later migrants—is often told with economic and cultural focus. However, a crucial dimension is their political engagement and contribution to the anti-apartheid struggle (roughly 1946–1994). This paper argues that the Indian diaspora served both as an internal actor within South Africa (through organisations like the Natal Indian Congress and the Transvaal Indian Congress) and as a conduit for international solidarity (including through the Indian state and global Indian communities). The dual role allowed them to bridge boundaries, between Indian and African communities, internal and international politics, and between colonial/indentured legacies and liberation politics.